Problems of Procedural Regularity in Labor Arbitration - Robben Wright Fleming (Washington University Law Quarterly, 1961)
This Article concerns difficult questions on which arbitrators themselves hold widely varying opinions. Such questions involve problems of fair procedure, without which industrial arbitration cannot hope to achieve stature and respect, and problems of industrial relations policy. The degree to which they should concern themselves with “good” industrial relations policy is debatable, both among arbitrators and the parties. After a brief introduction, this Article turns to a more careful examination of the problems which arise, the ways in which arbitrators have chosen to deal with them, and some of the policy considerations which are involved.
Keywords: Arbitration and award; Labor law